Test tube - Gonzalez, Carlos 1984- (Floating World Comics, 2015)
"Test Tube follows three people living in a faceless city of decrepit movie theaters, girlie nightclubs, and paper-thin apartment buildings. Within that stew, they are exposed to strange photographs, old cracked statues, cardboard cut-outs, and sexual mania. A stunning woman named Jill meets a white haired poet named Gene Dennel at the flea market. He invites her to collaborate on his masterpiece, revealing the secret that could spark the next phase of human evolution,"--Amazon.com
Offsetdruck
Keywords: Gonzalez, Carlos -- 1984-; Human evolution / Comic books, strips, etc; Secrecy / Comic books, strips, etc; Man-woman relationships / Comic books, strips, etc; Human evolution; Man-woman relationships; Secrecy; Comics (Graphic works); Graphic novels; Comic books, strips, etc; Graphzine